2015
DOI: 10.1111/pbi.12431
|View full text |Cite
|
Sign up to set email alerts
|

FT overexpression induces precocious flowering and normal reproductive development in Eucalyptus

Abstract: SummaryEucalyptus trees are among the most important species for industrial forestry worldwide. However, as with most forest trees, flowering does not begin for one to several years after planting which can limit the rate of conventional and molecular breeding. To speed flowering, we transformed a Eucalyptus grandis 9 urophylla hybrid (SP7) with a variety of constructs that enable overexpression of FLOWERING LOCUS T (FT). We found that FT expression led to very early flowering, with events showing floral buds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 40 publications
3
77
0
1
Order By: Relevance
“…To our knowledge, this is the first report of accelerated flowering and viable seed production in cassava using Arabidopsis FT . This study complements other reports of induced flowering [20,21,22,23,24,25,27], further highlighting the importance to continually develop efficient methods to foster flowering in cassava and other important crops. Similar to our grafting experiment, a recent field study also revealed a lack of flowering in non- or late-flowering cultivars grafted to rootstocks of a profuse, early flowering (non-transgenic) cultivar [28].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…To our knowledge, this is the first report of accelerated flowering and viable seed production in cassava using Arabidopsis FT . This study complements other reports of induced flowering [20,21,22,23,24,25,27], further highlighting the importance to continually develop efficient methods to foster flowering in cassava and other important crops. Similar to our grafting experiment, a recent field study also revealed a lack of flowering in non- or late-flowering cultivars grafted to rootstocks of a profuse, early flowering (non-transgenic) cultivar [28].…”
Section: Discussionsupporting
confidence: 85%
“…Once in the phloem, FT is translocated to the shoot apical meristem where interaction with the bZIP transcription factor FD and phospholipid phosphatidylcholine [16] results in nuclear localization and activation of LEAFY ( LFY ), APETALA1 ( AP1 ), and SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 ( SOC1 ) to trigger flower development [17,18,19]. With improved understanding of flowering mechanisms, over-expression of FT has been exploited to induce precocious flowering in various plant species [20,21,22,23,24,25] thus enabling a more rapid and refined approach to breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpressing FT in trees such as eucalypts promotes flowering and yields fertile flowers with viable pollen and seeds ( Fig. 1; Klocko et al, 2016), but as with most transgenes, the threshold level of expression can be variable among events. Apple transformed with MdFT1, citrus transformed with CiFT, and plum (Prunus domestica) transformed with CiFT and PtFT yielded fertile flowers, pollen, and seeds, respectively (Endo et al, 2005;Kotoda et al, 2010;Tränkner et al, 2010;Srinivasan et al, 2012).…”
Section: How Can Breeding Be Accelerated?mentioning
confidence: 99%
“…FT promoted flowering in Eucalyptus[45] as did expression from a heat-inducible promoter in juvenile poplar[43] (Figure 2) or by viral delivery into cotton, apple and pear [46,47,48,49 ]. Constitutive expression of poplar FT1 also gave early maturity and continuous flowering in plum [50] and its inducible expression promoted flowering in apple [51] (Figure 2).…”
mentioning
confidence: 99%